(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Dyslipidemia is an important risk factor for myocardial infarction, cardiovascular diseases, and Nonalcoholic Fatty Liver (NAFLD) disorders. Inflammatory conditions, oxidative stress, and insulin resistance, as well as several risk factors for cardiovascular disease, are also risk factors for this disease. This study aims to determine the effect of noni (Morinda citrifolia) extract on the improvement of dyslipidemia condition, based on the Low Density Lipoprotein (LDL) and High Density Lipoprotein (HDL) level. This research is a laboratory experimental study with a post-test only control group design. Male Wistar rat (Rattus norvegicus) were divided into four groups: negative control group with no induction and treatment (K-), positive control group given high-fat diet induction for 14 days (K+), noni extract treatment group given a high-fat diet and a noni extract at a dose of 100 mg/kg BB per day for 7 days (P1), and noni extract at a dose of 200 mg/kg BB per day for seven days (P2). Low Density Lipoprotein and High Density Lipoprotein serum levels were measured using the ELISA method. The results showed that there was a significant increase in LDL and a decrease in HDL in both treatment groups (P1 and P2) compared with K(+) group. Therefore, we conclude that noni extract (Morinda citrifolia) played a role as an antioxidant which can increase LDL and decrease HDL serum levels in rats induced by a high fat diet.